Why did she send it in the first place? Victim blame in the context of 'revenge porn'. Issue 3 (3rd May 2020) - Mckinlay, Tahlee; Lavis, Tiffany
Abstract : 'Revenge porn' or 'cyber rape' occurs when intimate images that were previously sent with permission are leaked to a wider audience without consent. This research investigated the perceptions that individuals form about 'revenge porn' victims, aiming to gain more understanding from a victimisation perspective as a first step towards improving victim outcomes. One hundred and twenty-two individuals were presented with a scenario depicting a leaked intimate image with a female victim. Two distinct nudity levels: low (lingerie) and high (bare-chest, breasts exposed) were included, and participants' responses to the Sexual Double Standards Scale were analysed to determine whether acceptance of the traditional sexual double standard was correlated with victim perception. Results indicated that victims were perceived as more promiscuous and more blameworthy when they were more naked, and by participants with more traditional gender roles. There is a need for policy to address potential stigma directed at 'revenge porn' victims.